The competing growth and optical performances of indium phosphide/titanium dioxide (InP/TiO2) composites. (31st May 2019) - Liu, Shuling; Xu, Yaya; Han, Xiaoli; Chai, Le
Abstract: Indium phosphide/titanium dioxide (InP/TiO2 ) microspheres were successfully synthesized via a facile one-step method. The as-prepared InP/TiO2 microspheres were composed of cubic phase InP and anatase TiO2 . InP/TiO2 microspheres were formed and obtained through the competing of InP nanoparticles and TiO2 nanoparticles. This special growth way improves the light absorption, increases specific surface area and changes the band gap of InP/TiO2, which are contributed to the photocatalysis degradation process. Especially, when using HCl as the inhibitor, under UV light, the InP/TiO2 composite possesses the remarkable photocatalytic activity for Congo red, which may be assigned to the superior optical performance and larger specific surface area.